Akuntabilitas Pengelolaan Dana Desa dan Dinamika Tata Kelola Lokal: Perspektif Good Governance di Kabupaten OKU Timur - Dafa, Pasha (Indonesian Journal Publisher, 2026)
This study examines the accountability of Village Fund management and local governance dynamics in Kabupaten OKU Timur, South Sumatra, from a good governance perspective. Using a qualitative approach, data were collected through in-depth interviews, document analysis, and field observations in selected villages. The findings indicate a gap between procedural compliance and substantive accountability. Although administrative reporting and financial documentation largely meet regulatory requirements, transparency remains largely formalistic and community participation is mostly limited to consultative processes. Local power relations, elite dominance, and differences in institutional capacity influence decision-making and resource allocation. Consequently, accountability practices tend to focus on administrative compliance rather than fostering genuinely participatory and socially accountable governance.